Kinetic of formation for single carbon dioxide and mixed carbon dioxide and tetrahydrofuran hydrates in water and sodium chloride aqueous solution - Sabil, Khalik M (Elsevier, 2010)
A laboratory-scale reactor system is built and operated to measure the kinetic of formation for single and mixed carbon dioxide-tetrahydrofuran hydrates. The T-cycle method, which is used to collect the kinetic data, is briefly discussed. For single carbon dioxide hydrate, the induction time decreases with the increase of the initial carbon dioxide pressure up to 2.96 MPa. Beyond this pressure, the induction time is becoming relatively constant with the increase of initial carbon dioxide pressure indicating that the liquid phase is completely supersaturated with carbon dioxide. Experimental results show that the inclusion of tetrahydrofuran reduces the induction time required for hydrate formation. These observations indicate hydrate nucleation process and onset growth are more readily to occur in the presence of tetrahydrofuran. In contrast, the presence of sodium chloride prolongs the induction time due to clustering of water molecules with the ions and the salting-out effects. It is also shown that the degree of subcooling required for hydrate formation is affected by the presence of tetrahydrofuran and sodium chloride in the hydrate forming system. The presence of tetrahydrofuran in the hydrate system significantly reduces the amount of carbon dioxide uptake. The apparent rate constant, k, for those systems are reported.